2016
DOI: 10.1016/j.jallcom.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Stability of fluorite-type La2Ce2O7 under extreme conditions

Abstract: a b s t r a c tThe structural stability of fluorite-type La 2 Ce 2 O 7 was studied at pressure up to~40 GPa and under hydrothermal conditions of~1 GPa and up to 350 C, respectively, using synchrotron X-ray diffraction (XRD) and Raman scattering measurements. XRD measurements indicated that the fluorite-type La 2 Ce 2 O 7 is not stable at pressures greater than 22.6 GPa and gradually transformed to a high-pressure phase. The highpressure phase is not stable and changeed back to the fluorite-type structure when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Therefore, the Raman peak of the La 2 Ce 2 O 7 ‐based samples at ≈ 445 cm –1 is assigned to the F 2g mode of the defective cubic fluorite phase, and the band at ≈ 575 cm –1 is assigned to the surface oxygen vacancies originated from the incorporation of La 3+ into CeO 2 lattice. In detail, to maintain the overall charge, oxygen vacancies are formed, which can dissociatively adsorb O 2 molecules and generate surface mobile oxygen species , . To confirm this, the Raman spectra in the region of 950–1200 cm –1 are enlarged for the samples and shown in Figure b.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, the Raman peak of the La 2 Ce 2 O 7 ‐based samples at ≈ 445 cm –1 is assigned to the F 2g mode of the defective cubic fluorite phase, and the band at ≈ 575 cm –1 is assigned to the surface oxygen vacancies originated from the incorporation of La 3+ into CeO 2 lattice. In detail, to maintain the overall charge, oxygen vacancies are formed, which can dissociatively adsorb O 2 molecules and generate surface mobile oxygen species , . To confirm this, the Raman spectra in the region of 950–1200 cm –1 are enlarged for the samples and shown in Figure b.…”
Section: Resultsmentioning
confidence: 87%
“…However, for poorly crystallized CeO 2 possessing a lot of surface and bulk defects, another peak at ≈ 600 cm –1 corresponding to surface oxygen vacancies can also be observed , . In addition, the doping of La 3+ into CeO 2 lattice can shift the F 2g peak to a lower wavenumber , . Therefore, the Raman peak of the La 2 Ce 2 O 7 ‐based samples at ≈ 445 cm –1 is assigned to the F 2g mode of the defective cubic fluorite phase, and the band at ≈ 575 cm –1 is assigned to the surface oxygen vacancies originated from the incorporation of La 3+ into CeO 2 lattice.…”
Section: Resultsmentioning
confidence: 99%
“…Table 6 summarizes linear thermal expansion coefficients (α) for various A 2 B 2 O 7 compounds in the 400 to 1000 • C range. It should be noted that La 2 Ce 2 O 7 , unlike the other oxides in Table 6, is not a pyrochlore and instead adopts a disordered fluorite type structure, where the cations are randomly distributed in the cation sublattice [243][244][245][246].…”
Section: Pyrochlore-and Fluorite-related Structuresmentioning
confidence: 99%
“…Several authors report good stability of the cubic-type ionic conductors under WGS experimental conditions. Zhang et al [48] studied the stability of fluorite-type La 2 Ce 2 O 7 under wet conditions and found that a pressure of 1 GPa is necessary to modify the structure. Moreover, the introduction of Zr was reported to enhance the stability of the ionic conductors [49,50].…”
Section: Kinetics Study On Structured Catalystmentioning
confidence: 99%